Relief seed assistance in Zimbabwe - Bramel-Cox, P.J.; Remington, T.; Nagoda, S.; Haugen, J.; Sperling, L. (2004)
Zimbabwe has been a recipient of food or seed aid since the 1990/91 drought, considered one of the worst in 100 years. At present, as in the past, interventions aimed at agricultural rehabilitation and recovery have focused on direct seed distribution ("seeds and tools"). While these interventions are being modified to better address the needs of farmers recovering from disaster, they are still based upon the premise that the emergency has resulted in a loss of seed and other assets, and there is a need to supply them. This study of relief seed intervention in Zimbabwe addresses a number of issues: (1) the effectiveness of the past agricultural recovery response to disasters, (2) knowlegde of farmers' seed systems, (3) changes in seed systems as influenced by relief seed distributions, and (4) the cause of the continual need for seed assistance.